2018
DOI: 10.1002/mabi.201800159
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of Biodegradable and pH‐Responsive Polysuccinimide Nanoparticles (PSI‐NPs) as Smart Nanodelivery Systems in Grapefruit: In Vitro Cellular Investigation

Abstract: Biodegradable pH-responsive polysuccinimide nanoparticles (PSI-NPs) are synthesized for directly delivering agrochemicals to plant phloem to improve their efficacy. The PSI-NPs have an average size of 20.6 nm with negative charge on the surface. The desired responsiveness to changes in pH is demonstrated by release efficiency of the model molecule (Coumarin 6), which increases with increasing pH over 24 h. The internalization of PSI-NPs into grapefruit cells occurs in 10 min, and into nucleus in 2 h, with most… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 32 publications
0
21
0
Order By: Relevance
“…When the chemically loaded NPs reach the phloem, the relatively high pH environment triggers the release of effective compounds along with degradation of NPs. The accessibility of NPs to grapefruit cells and pH-responsive release has been confirmed in in vitro experiments (Xin et al 2018). Limited biological toxicity of polysuccinimide-NPs (up to 200 mg L À1 ) to citrus seedlings (Hill et al 2015) and soil microbes (Xin et al 2018) was also observed.…”
Section: Nano-delivery Systems Definitionmentioning
confidence: 81%
See 2 more Smart Citations
“…When the chemically loaded NPs reach the phloem, the relatively high pH environment triggers the release of effective compounds along with degradation of NPs. The accessibility of NPs to grapefruit cells and pH-responsive release has been confirmed in in vitro experiments (Xin et al 2018). Limited biological toxicity of polysuccinimide-NPs (up to 200 mg L À1 ) to citrus seedlings (Hill et al 2015) and soil microbes (Xin et al 2018) was also observed.…”
Section: Nano-delivery Systems Definitionmentioning
confidence: 81%
“…For example, CNTs could adsorb a range of organic contaminants from soil, such as organophosphorus pesticides, organochlorine pesticides, pharmaceuticals and personal care products, and pyrethroid insecticides (Jakubus et al 2017). Given their hydrophilic exterior and hydrophobic interior, polymeric NPs have been used to encapsulate lipid soluble drug molecules for targeted nanodelivery to improve stability, bioavailability and controlled release of the encapsulated drugs (Xin et al 2018). Covalent binding of Ag NPs onto cotton fabric through carboxymethyl chitosan was reported as an effective method for obtaining antimicrobial functions and outstanding laundering durability (Xu et al 2018a).…”
Section: Mechanisms Of Nano-delivery Systems Loadingmentioning
confidence: 99%
See 1 more Smart Citation
“…The most practical and common approach is foliar spraying; however, this was shown to be relatively ineffective in citrus as a means to deliver bactericides such as oxytetracycline to inhibit C Las 65 . Multiple research groups are evaluating alternative approaches, such as trunk injection and/or nanoparticle-based systems 65 , 66 . Potato plants are relatively easier to handle and are amenable to foliar spraying techniques.…”
Section: Resultsmentioning
confidence: 99%
“…An example is a system based on poly(succinate), which is a biodegradable hydrophilic biopolymer that is liable to hydrolysis at alkaline pH [36]. Hill et al [27, 72] developed a poly(succinate) nanocarrier system intended for the control of diseases affecting plant phloem. The pH of most plant tissues is acidic, while that of the vascular phloem tissue is alkaline.…”
Section: Applications Of Stimuli-responsive Systems In Agriculturementioning
confidence: 99%